Diet and Lifestyle Changes During the COVID-19 Pandemic in Ibero-American Countries: Argentina, Brazil, Mexico, Peru, and Spain - Enriquez-Martinez, Oscar G.; Martins, Marcia C. T.; Pereira, Taisa S. S.; Pacheco, Sandaly O. S.; Pacheco, Fabio J.; Lopez, Karen V.; Huancahuire-Vega, Salomon; Silva, Daniela A.; Mora-Urda, Ana I.; Rodriguez-Vásquez, Mery; Montero López, M. Pilar; Molina, Maria C. B. (Frontiers in Nutrition, 2021)
This study aimed to evaluate changes in dietary and lifestyle habits during confinement due to COVID-19 pandemic in Ibero-American countries. A cross-sectional investigation was conducted with 6,325 participants of both genders (68% women), over 18 years of age and from five countries: Brazil (N= 2,171), Argentina (N= 1,111), Peru (N= 1,174), Mexico (N= 686), and Spain (N= 1,183). Data were collected from July to September 2020 using a self-administered online survey designed for the assessment of sociodemographic, employment, physical activity, health status, and dietary habits changes during the confinement. Most participants (61.6%) remained constant in their pattern of food consumption. However, among those who changed, a healthier pattern prevailed (22.7%), with an increase in the frequency of consumption of fruits, vegetables, legumes and a decrease in snacks and bakery products. These individuals showed a tendency to gain weight. The pandemic situation also contributed to a trend in reducing the consumption of main meals and in increasing the consumption of small meals and snacks. Argentina and Brazil showed highest proportion of changes toward a healthier pattern of food consumption. There was a lower prevalence of change towards a less healthy pattern of food consumption among Spanish participants. Peruvians and Mexicans were less likely to make healthy changes in food consumption (OR: 0.51; 95% CI: 0.4-0.6 and OR: 0.69; 95% CI: 0.4-0.8, respectively), when compared to Argentinians. Individuals with alterations in sleep pattern were more likely to change their diets to a healthier pattern. In contrast, individuals with confirmed diagnosis of COVID-19 and those who reported feeling anxious were more likely to perform changes to a less healthy eating pattern (OR: 1.72; 95% CI: 1.2-2.3 and OR: 1.21; 95% CI: 1.1-1.4, respectively). In conclusion, although most participants remained constant in their eating habits, lifestyle changes and anxiety feelings were reported. Among those who changed patterns of food consumption, healthier choices prevailed, with differences between countries. However, there were alterations in the distribution of meals, with higher consumption of snacks and small meals. These results can be used to guide policies to prevent deleterious consequences that may affect incidence of chronic diseases.